PENETAPAN KADAR VITAMIN C PADA BUAH NANAS KALENG (Ananas comocus L.) DENGAN METODE SPEKTROFOTOMETRI UV-Vis DAN TITRASI IODIMETRI - Ruwista, Anista; Sugiyo, Warlan; Mahesa, Sandi (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2021)
Vitamin C has an important role in the human body, namely carrying out its functions such as in the synthesis of collagen, the formation of carnitine, is involved in cholesterol metabolism, become bile acids, and plays an important role in the formation of the neurotransmitter norepinephrine. Vitamin C intake must be obtained from outside the body because this vitamin cannot be synthesized in the body through the biosynthetic pathway. Pineapple fruit is one of the fruits that contain vitamin C. The purpose of this study was to analyze the levels of vitamin C in canned pineapples for which the result of vitamin C on the AKB value on the packaging label were not known using UV-Vis spectrophotometry and iodimetric titration. The method used in the qualitative analysis of vitamin C is identification by color raction using Fehling A and B reagents and KMnO4 reagent. Quantitative analysis of vitamin C using the UV-Vis spectrophotometry method with a wavelength of 0,0031 % while the results from the iodimetric titration methode obtained an average % of vitamin C levels from canned pineapple samples of 0,050 % w/w.